(untitled) (Journal of Informatics Education and Research, 2025)
India, the cradle of one of the world’s oldest and most enduring civilizations, has long been a beacon of spirituality, attracting seekers from across the globe. As the birthplace of Yoga, Ayurveda, and several major religions—including Hinduism, Buddhism, and Jainism—India is revered for its sacred landscapes and profound spiritual heritage. Pilgrimage sites such as Varanasi, Rishikesh, Prayagraj, Bodh Gaya, and Amritsar continue to draw millions in search of enlightenment and inner peace. Maha Kumbh 2025 was uniquely positioned as an once-in-a-lifetime spiritual experience due to an exceptionally rare celestial alignment that occurs once every 144 years. Pilgrims from around the world gathered at Prayagraj - Triveni Sangam—the confluence of the Ganga, Yamuna, and Saraswati—to participate in this 45-day festival, seeking spiritual renewal and the promise of Moksha (liberation). This study explores how Maha Kumbh 2025 was curated as a transformative spiritual event through the lens of the Experience Economy framework (Pine & Gilmore, 1998). By integrating its deep-rooted spiritual essence with modern digital marketing strategies, AI-driven personalization, and cultural storytelling, the event was positioned as a deeply immersive experience. The case study highlights how Maha Kumbh 2025 was curated as a spiritual experience, resonating with both devout pilgrims and a global audience.